A review of EU biocides and pesticides legislations - Elsmore, Richard; Chapman, Peter (International pest control, 2013)
The development of both agricultural pesticides legislation and biocides legislation in the European Union (EU) has followed a similar course during the past two decades. Pesticides were the first to be subject to EU-wide legislation with the introduction of the Plant Protection Products Directive, 91/414/EEC coming into force on Jul 26, 1993. Biocides followed with the introduction of the Biocidal Products Directive, 98/8/EC, coming into force on May 14, 2000. Pesticides principally include products that are used in agriculture and horticulture for the control of pests, diseases and weeds and as plant growth regulators. Biocides are a broad group of products that are used to control unwanted organisms in many differing areas. This article is intended to provide some high level comparisons between the new regulations governing the approval and authorisation of both biocide and pesticide active substances and products.